2013
DOI: 10.1016/j.molonc.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Glioma‐derived macrophage migration inhibitory factor (MIF) promotes mast cell recruitment in a STAT5‐dependent manner

Abstract: Recently, glioma research has increased its focus on the diverse types of cells present in brain tumors. We observed previously that gliomas are associated with a profound accumulation of mast cells (MCs) and here we investigate the underlying mechanism. Gliomas express a plethora of chemoattractants. First, we demonstrated pronounced migration of human MCs toward conditioned medium from cultures of glioma cell lines. Subsequent cytokine array analyses of media from cells, cultured in either serum-containing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 31 publications
1
38
0
Order By: Relevance
“…H). While MIF has been implicated in multiple cancers outside of the central nervous system and its activation of tumor immune suppression is well documented , its role as a mediator of a GBM CSC/tumor‐infiltrating MDSC interaction was previously unknown. Further, the finding that CXCR2, but not CXCR4, facilitated MIF‐driven MDSC function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…H). While MIF has been implicated in multiple cancers outside of the central nervous system and its activation of tumor immune suppression is well documented , its role as a mediator of a GBM CSC/tumor‐infiltrating MDSC interaction was previously unknown. Further, the finding that CXCR2, but not CXCR4, facilitated MIF‐driven MDSC function (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Roy et al [54] investigated the recruitment pattern of MCs to glioma tumors and reported that glioma-derived plasminogen activator inhibitor-1 (PAI-1) promotes MC recruitment and that the level of PAI-1 correlates with the rate of MC recruitment. Additionally, macrophage migration inhibitory factor (MIF) released by glioma cells contributes to the recruitment of MCs by inducing phosphorylation of STAT5 [55]. Also, glioma cells release CXCL12 that acts as MC chemotaxin by engaging CXCR4 [56] (Fig.…”
Section: Mast Cell Recruitment To Tumormentioning
confidence: 99%
“…Human brain cancer tissue microarray (TMA) BS170154a was purchased from US Biomax (Derwood, MD). A second set of TMAs contained high‐grade glioma (HGG, 102 cases), low‐grade glioma (LGG, 80 cases), and nonmalignant control brain tissue has been described elsewhere . TMAs were subjected to immunostaining applying antiheparanase (antibody 733) and anti‐CD24 (Novus Biologicals; Littleton, CO) antibodies, essentially as described …”
Section: Methodsmentioning
confidence: 99%